Um estudo dos registros contábeis sobre os impactos do imposto de renda e contribuição social, apurados pelo regime do lucro real em uma transação de combinação de negócios, por meio de incorporação e incorporação reversa no mercado brasileiro - Constantino, Anderson Pascoal (2012)
In today s marketplace where globalization is essential for Companies the acquisition or business association is essential for aim their growth business and become more competitive. These acquisitions are solely aimed at unifying the market and achieving growth for their shareholders profits. Nonetheless, regulators dedicate significant time to issue technical standards and to conduct studies addressing the accounting and tax treatment applicable to these transactions. Since the implementation of the new accounting standards (CPC Brazilian Financial Accounting Standards Board) that began on 2008 and completely implemented on 2010, and these standards are harmonized with the International Financial Reporting Standards (IFRS), a significant number of questions and professional judgment have given rise to of new accounting standards. The new accounting standards issued related of acquisition, goodwill and income tax have not presented clearly, which are the necessary accounting entries to demonstrated the income tax impact in the initial and after the business combination acquisition with incorporation or reverse incorporation. This lack of explicitness generated for two reasons: a) the new accounting standards are basically the translation from the IFRS International Financial Reporting Standard, so the new accounting standards are harmonized; b) the Brazilian income tax s Law is different from the income tax s Law of the region that the international accounting standards were initially composed. The income tax rules adapted for the new accounting standards, but there are differences between the new accounting standards and the income tax rules, as the goodwill amortization originated from a business combination that for income tax is still amortized and for accounting this amortization is not permitted. The main objective of this study was analyzed which are the necessary accounting entries to demonstrated the income tax impact under a business combination through incorporation or reverse incorporation. This is consider a qualitative research with focus on exploratory study that was developed through a case study, which are analyzed public information related of Financial Statement of publicly-held corporation whose shares are trade related at the year ended on December of 2010. This research verified that the companies analyzed are using the rational associated with the accounting and tax of the new standards and apparently the accountant are properly interpreted the new accounting standards